2004
DOI: 10.1007/bf03168443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leptin on renal ischemia-reperfusion damage in rats

Abstract: Tumor necrosis factor-alpha (TNF-alpha) has been established as an important mediator in renal ischemia-reperfusion (I/R) injury. Leptin, a product of the ob gene, has been known to exhibit cytoprotective effects on renal tissue, but its effect on renal tissue TNF-alpha level after renal I/R injury in rats remains unknown. The purpose of the study was to evaluate the effects of leptin on renal tissue TNF-alpha, malondialdehyde (MDA), protein carbonyls (PCs) and total sulfydryl group (SH) levels, and plasma nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
(26 reference statements)
1
32
1
Order By: Relevance
“…24 Leptin-stimulated ROS production and NO synthesis has been shown also to protect against ischemia reperfusion injury in the gut and kidney. 162,163 Clinically, it is interesting to note that patients with a higher body mass index have better outcomes following an acute coronary syndrome or percutaneous coronary intervention. 164,165 Leptin Resistance in the Cardiovascular System?…”
Section: Protection In Ischemia/reperfusion Injurymentioning
confidence: 99%
“…24 Leptin-stimulated ROS production and NO synthesis has been shown also to protect against ischemia reperfusion injury in the gut and kidney. 162,163 Clinically, it is interesting to note that patients with a higher body mass index have better outcomes following an acute coronary syndrome or percutaneous coronary intervention. 164,165 Leptin Resistance in the Cardiovascular System?…”
Section: Protection In Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Our previous studies reported that leptin has a protective effect on renal I/R model induced by 1 hour of ischemia following 1 hour of reperfusion (1). Another study showed the protective effects of resveratrol against oxidative stress on cardiac I/R model in the same time periods (2).…”
Section: Introductionmentioning
confidence: 97%
“…myocardium; ischemia-reperfusion injury; Janus-activated kinase/signal transducer and activator of transcription signaling THE ADIPOCYTOKINE LEPTIN has been shown to protect against ischemia-reperfusion (I/R) injury in various tissues including kidney (9), gut (6), and brain (34). Recently, we reported that leptin, administered at reperfusion, also protects the myocardium against I/R-induced damage (24).…”
mentioning
confidence: 99%